EVALUASI PINDAH PANAS KOTAK PENDINGIN DARI PADUAN SEKAM PADI DENGAN RESIN - Ni Kadek Elvin Artika; Sukmawaty Sukmawaty; Guyup Mahardhian Dwi Putra (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2018)
Rice husk is agricultural waste that can still be functioned as heat insulator. The purpose of this study was to analyze the heat transfer occurring in cooling box made from combination of rice husk and resin. From the resulted test, the lowest thermal conductivity value of rice husk cooling box ranged from 0.111 to 0.289 W/m2K. While the highest thermal conductivity of styrofoam boxes ranged from 0.204 to 0.986 W/m2K. The difference in material thermal conductivity value will cause difference in total heat transfer rate generated. The lowest convection transfer coefficient occurred at styrofoam box with value ranged from 2.812 to 5.045 W/m2 K, while the lowest occurred at rice husk box with value ranged from 1.717 to 2.217 W/m2K. The highest thermal resistance was 10.981Â°C/W of the rice husk box, while the lowest was 4,156Â°C/W of the styrofoam box. The thermal resistance indicates the ability of a material to resist the rate of heat transfer. The highest total heat transfer rate was found in the styrofoam box of 12.632 W, while the lowest was in the rice husk box of 11.845 W. The low heat transfer rate in the rice husk box indicated that the rice husk was able to resist transferred heat properly.